Odpowiedzi

2009-12-07T18:40:04+01:00
0,4x + 0,3y = 1,4/*10
0,1x + 3y = 2,3/*10

4x+3y=14
x+3y=23

4x+3y=14
x=23-3y

4*(23-3y)+3y=14
x=23-3y

92-12y+3y=14
x=23-3y

-12y+3y=14-92
x=23-3y

-9y= -78/:(-9)
x=23-3y

y=8,6
x=23-3y

y=8,6
x=23-3*8,6

y=8,6
x=23-25,8

y=8,6
x=-2,8
••••••••••••••

2x + 3y = 14
3x - 2y = 8

5x+y=22
y=22-5x

2x + 3y = 14
y=22-5x

2x+3(22-5x)=14
y=22-5x

2x+66-15x=14
y=22-5x

2x-15x=14-66
y=22-5x

-13x=-52/:(-13)
y=22-5x

x=4
y=22-5x

x=4
y=22-5*4

x=4
y=22-20

x=4
y=2

••••••••••••••••••

1/2x - 2y = 8/*2
2x + 5y = 6

x-4y=16
2x + 5y = 6

x=16+4y
2x+5y=6

x=16+4y
2(16+4y)=6

x=16+4y
32+8y=6

x=16+4y
8y=6-32

x=16+4y
8y=-26/:8

x=16+4y
y=-3,25

x=16+4*(-3,25)
y=-3,25

x=16-13
y=-3,25

x=3
y=-3,25

••••••••••••••••••••••••

1/2x - 3/4y = 0
2/3x + 1 1/4y = 9


1/2x - 3/4y = 0 /*2
2/3x+5/4y=9/*12

x-1,5y=0
8x+15y=108

x=1,5y
8x+15y=108

x=1,5y
8*1,5y+15y=108

x=1,5
12y+15y=108

x=1,5
27y=108/:27

x=1,5
y=4
••••••••••••••••••••

3x + 4y = 1 2/3
6x + 3y = 1 1/4

3x+4y=5/3/*3
6x+3y=5/4/*4

6x+12y=5/*(-1)
24x+12y=5

-6x-12y=-5
24x+12y=5

18x=0/:18
x=0

24x+12y=5
x=0

24*0+12y=5
x=0

0+12y=5
x=0

12y=5/:12
x=0

y=5/12
x=0